Evaluation Metrics of Electronic Learning Resources Quality - Kravtsov, H. (Journal of Information Technologies in Education (ITE), 2009)
The results of measuring modeling of educational materials qualitative characteristics for monitoring providing of electronic learning information resources quality of institution of higher education are presented. Distance learning system «Kherson Virtual University» is used as illustration.